Clinical and therapeutic correlations in patients with slight acute pancreatitis - MUNHOZ-FILHO,Clewis Henri (2015)
BACKGROUND: Acute pancreatitis is an inflammatory disease of the pancreas due to enzymatic autodigestion which can cause necrosis or multiple organ failure; its pathophysiology is not fully known yet. AIM: To evaluate the correlation between clinical and therapeutic data in patients with mild acute pancreatitis. METHODS: A retrospective study in 55 medical records of patients admitted with acute mild pancreatitis was realized to analyze the association between age, leukocytosis, serum glutamic-oxaloacetic transaminase and lactate dehydrogenase, glucose, antibiotics, time admission and Ranson´s scores. RESULTS: There was a positive association between less intensive care (strict hydration, analgesia and monitoring of vital signs), early antibiotic therapy (monotherapy), early return to diet after 48 hours and laboratory control of the serum amylase and lipase (high in the first week and decreasing after 10 days, without any prognostic value). CONCLUSIONS: Changes in the management of patients with mild acute pancreatitis, such as enteral nutrition, rational use of lower spectrum antibiotics and intensive care, have contributed significantly to the reduction of hospitalization time and mortality.